Investigação da atividade antitumoral e anti-angiogênica da violaceína em co-culturas de células leucêmicas e células endoteliais - Palladino, Marcelly Valle [UNIFESP] (2018)
Introduction: The bone marrow microenvironment is a milieu complex of various types of stromal and hematopoietic cells involved in the selfrenewal and differentiation of stem cells and hematopoietic progenitors (HSPC). Several soluble and membranebound factors produced by endothelial cells (EC) and perivascular stroma are crucial signals to maintain quiescence and facilitate the return to homeostasis after myeloablative chemotherapy. In addition, several studies have shown a relationship between HSPCs and ECs, pointing to hemangioblastic activity in HSPCs, both in the generation of cells and blood vessels. Considering the relationships between HSPCs and CSs in the bone marrow, it is possible to implicate CDEs in the establishment and progression of malignant HSPCs such as acute and chronic myeloid leukemias. In fact, in leukemias, studies have shown that angiogenesis also contributes to its pathogenesis, with an increase in bone marrow vascularization, associated with elevated levels of angiogenic factors. Thus, therapeutic strategies that aim to inhibit the angiogenic process may aid in the treatment of leukemia. OBJECTIVE: The objective of this study was to investigate the antiangiogenic effect of violacein on rabbit aortic endothelial cell (RAEC) and leukemic cells from the K562 and Lucena1 (K562 with MDR1 phenotype) lines. Results: It was observed that violacein, at concentrations lower than its IC 50, is able to inhibit capillary tube formation, proliferation, migration and invasion of ECs, with IC50 of RAEC cells (5.0 μM) higher than IC 50 Of the leukemic cells (3.5 μM). When RAEC cells were cocultured with leukemia cells in direct contact, in the presence of inserts or with the conditioned medium of the leukemic cells, an increase in proliferation, capillary formation, migration and invasion of RAEC cells was observed. In addition, the increase in these parameters was higher in cocultures with the Lucena1 lineage. In contrast, pretreatment of leukemic cells with violacein significantly reduced these effects, with inhibition of the VEGFR2 / PI3K / AKT and VEGFR2 / Src / MAPK pathways in the studied strains (ECs and leukemias). Taken together, the results show the importance of soluble factors in the modulation of the events associated with the angiogenic process and demonstrate the antiangiogenic potential of violacein with action in important ways of regulating angiogenesis and cell proliferation.